Investigation of the viability of selected microorganisms on the biodegradation of Palm Oil Mill Effluent(POME) - Abass Olanrewaju, Alade; Jameel, Ahmed Tariq; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail; Alam, Md Zahangir (World Academy of Research and Publication, 2012)
Biodegradation of palm oil mill effluents (POME) by three microorganisms namely Trichoderma viride, (Tv), Candida cylindricea (Cd) and Phaneaochaete chrysospium (Pc), were conducted in batch aerobic reactors. The autoclaved and un-autoclaved raw POME samples were agitated at 150rpm, incubated for 5days and the activities of the microorganisms were terminated at -200C. The supernatant of the digested POME were investigated for the removal of chemical oxygen demand (COD), biochemical oxygen demand (BOD), total dissolved solids (TDS), conductivity and biosolids at the end of each digestion cycle. The results showed that the un-autoclaved raw POME sample degraded better than the inoculated POME sample and this suggests that the microorganisms that are indigenous to the POME are more effective than the introduced microorganisms. This result, however, indicates the prospect of isolating indigenous microorganisms in the POME for effective biodegradation of POME.